Language Learning and the Indian Education System: Does the Indian Education System Steer Students Away from Language Learning and Acquisition? - Pimpalgaonkar , Prutha; Rajan, Garima (Cultural Arts Research and Development, 2024)
The development of language is a pivotal process in human beings. While the terms ‘language acquisition’ and ‘language learning’ are used interchangeably—they are vastly different—and work together to facilitate language development. Looking at multilingual societies, research diverges in two directions: one side states that multilingualism in the educational sphere can aid conscious language learning and the other that it can restrict the same. India’s case is interesting—although a majority of the population is at least bilingual, with most being able to speak three languages— this ability appears to be a result of environmental factors more than it does of the educational system, even though the latter actively promotes multilingualism. This paper analysed the Three-Language Formula (TLF) which is the basis of the Central Board of Secondary Education’s (CBSE) curriculum in India, as well as the teaching strategies in schools using a comprehensive secondary research methodology. It was found that while the policies in place are cognitively beneficial for students, considering simultaneous instruction of language is used, it is their inconsistent implementation through teaching methodologies that steers students away from further language learning. It is necessary that a shift is made away from the hierarchical treatment of languages through unregulated teaching practices and towards real-world multilingualism, which provides equal support for each language in the subcontinent.